Genetic characterization and protein stability analysis of a Chinese family with Von Hippel-Lindau disease - Gao, Yong; Huang, Yan-ping; Tu, Xiang-an; Luo, Dao-sheng; Wang, Dao-hu; Qiu, Shao-peng; Xiang, Peng; Li, Wei-qiang; Jan, Rohozinski; Zhang, Yuan-yuan; Sun, Xiang-zhou; Deng, Chun-hua (Chinese medical journal, 2013)
Background Von HippeI-Lindau disease （VHL）,a heritable autosomal dominant disease characterized by neoplasia in multiple organ systems,has rarely been reported in Asia.We genetically investigated a unique Chinese family with VHL disease and performed an analysis of the VHL protein stability.Methods Genomic deoxyribonucleic acid （DNA） extracted from peripheral blood was amplified by polymerase chain reaction （PCR） to three exons of the VHL gene in 9 members of the Chinese family with VHL disease.PCR products were directly sequenced.We estimated the effects of VHL gene mutation on the stability of pVHL,which is indicated by the free energy difference between the wild-type and the mutant protein （△△G）.Results The Chinese family was classified as VHL type 1.Three family members,including two patients and a carrier,had a T to G heterozygotic missense mutation at nucleotide 515 of the VHL gene exon 1.This missense mutation resulted in the transition from leucine to arginine in amino acid 101 of the VHL protein.There was low stability of the VHL protein （the △△G was 12.71 kcal/mol） caused by this missense mutation.Conclusions We first reported a family with this VHL gene mutation in Asia.This missense mutation is predicted to significantly reduce the stability of the VHL protein and contribute to the development of the renal cell carcinoma （RCC） phenotype displayed by this family.The genetic characterization and protein stability analysis of families with VHL disease are important for early diagnosis and prevention of the disease being passed on to their offspring.